ANALISIS KUALITAS PELAYANAN PEMOTONGAN SAPI PADA PT. RPH SURABAYA PERSERODA - Muthowif; Siti Lailuatus Sofiyah; Nur Solikin (Jurnal Agriovet, 2026)
The availability of safe, healthy, whole, and halal (ASUH) meat is an important aspect in protecting public health and part of public services in the field of veterinary public health. Slaughterhouses (RPH) have a strategic role in ensuring that the animal slaughtering process and carcass handling are carried out in accordance with sanitation standards, animal welfare, and halal requirements. This study aims to analyze the quality of cattle slaughter services in realizing ASUH meat. The research location is PT Rumah Potong Hewan (RPH) Surabaya Perseroda, implemented from Oktober to Desember 2025. The study used a qualitative approach with a descriptive design to deeply understand the service practices that take place in the field. Informants were determined purposively consisting of Slaughterhouse management, veterinarians, operational officers, halal slaughterers, and service users. Data collection techniques were carried out through observation, in-depth interviews, and documentation, while data analysis used an interactive model through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the quality of cattle slaughter services at PT RPH Surabaya Perseroda has generally run quitewell based on service quality dimensions that include physical evidence, reliability, responsiveness, assurance, and empathy. Pre- and post-slaughter animal health inspections, implementation of halal slaughter procedures, and veterinary supervision are crucial factors in maintaining meat quality. Future recommendations include improving supporting facilities and strengthening operational management to ensure the continued optimal supply of ASUH meat. Key words: Service quality, slaughterhouse, ASUH meat, public service, food  safety